ANALISIS DAN INTERPRETASI CAIRAN SEREBROSPINAL (LCS) DALAM PERAWATAN NEUROKRITIS UNTUK KONDISI NEUROLOGIS AKUT, ARTIKEL REVIEW - Sinulingga, Anselmus Libreya; Sangging, Putu Ristyaning Ayu; Soleha, Tri Umiana (CV. Jasa Sukses Abadi, 2024)
Cerebrospinal fluid (LCS) is a clear fluid circulating in the intracranial and spinal compartments. Under normal conditions, the composition of LCS remains constant. However, in various neurological disease especially in acute conditions, the composition, quantity and its pressure can be altered. The importance of CSF in the diagnosis of neurological diseases has been enhanced with the development of techniques that allow direct measurement or indirect analysis of CSF composition. These methods not only aid in diagnosis but also in assessing the severity and prognosis of the neurological conditions faced by patients. For instance, measuring glucose levels in CSF can help differentiate between subarachnoid hemorrhage due to an aneurysm and other types of hemorrhagic stroke. By measuring the levels of various LCS components using relevant techniques, diagnosis, severity and prognostication of neurological conditions like infections, subarachnoid hemorrhage, demyelinating conditions, tumor like conditions, etc. can be done. In the context of emergency care, a good understanding of changes in CSF and their relevance to the patient's clinical condition enables doctors to make more accurate decisions regarding management and treatment. Therefore, CSF analysis is crucial not only for initial diagnosis but also for monitoring and assessing the response to therapy. In this review, alterations in LCS components and its relevance to the emergency care physician to help in the management of patients are enumerated.